Aplikasi Pemesanan Dengan Fitur Custom Menu Berbasis Web Mobile Application Booking With Features Custom Menu Based Web Mobile (Information Technology and Telematics, 2015)
Abstract--  Development of technology in the field of information makes its users feel easier in d oing their duty or  their needs. Recording customer order on the spot entry directly location restaurant usually did by using the stationery, such pen and notes or using the computer like in the fast food restaurants do.Application  order  menu  uses  PC  (Personal  Computer)  kitchen  server  or  cashier  server  and  the  customers  use tablet  android.Use  of  application  ordering  in  the  restaurant  makes  use  of  Macromedia  Dreamweaver  CS6,  MySQL database, and modern TP-Link TD-W8151N for the internet connection. Use of web mobile for ordering menu can help business process in a restaurant and can help customers in order to be easier in booking  or ordering the menu. With the  fitur custom menu, we can  order the additional menu as  customers’ taste.  Furthermore,  it  makes  admin  to  be  easier  in  the  process  of  transaction  data  recapitulation  daily,  monthly,  even annually.Keywords: Website, web mobile, PHP, MySQL, Information